2017
DOI: 10.1007/s11606-017-4059-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Use of Benzodiazepines among Older Adults in Israel: Epidemiology and Leverage Points for Improvement

Abstract: Benzodiazepines/BDZRAs are used at exceptionally high rates by older Israeli adults, especially the oldest old. Important leverage points for quality improvement efforts include curtailing the transition from short-term to long-term use, reducing use in older adults with depression, and identifying reasons that explain large differences in benzodiazepine/BDZRA prescribing between different ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
(47 reference statements)
5
11
3
Order By: Relevance
“…In agreement with our findings, BZDC increased with age in other national and international surveys 28 -30 However, our findings showed that consumption after age 60 was lower than among those in the 49-59 age stratum, a somewhat suprising fact, as older individuals are described as the leading group of BZD users in many studies 25,26. Corroborating our finding, another study showed that long-term use of sedatives increased between 2004 and 2013 driven largely by increased use among middle-aged adults31 It also bears stressing that lifetime BZDC among adolescents (2.7%) was lower than previously reported in a Brazilian study (5%)32 and in a European study (5.6%) 33.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, BZDC increased with age in other national and international surveys 28 -30 However, our findings showed that consumption after age 60 was lower than among those in the 49-59 age stratum, a somewhat suprising fact, as older individuals are described as the leading group of BZD users in many studies 25,26. Corroborating our finding, another study showed that long-term use of sedatives increased between 2004 and 2013 driven largely by increased use among middle-aged adults31 It also bears stressing that lifetime BZDC among adolescents (2.7%) was lower than previously reported in a Brazilian study (5%)32 and in a European study (5.6%) 33.…”
Section: Discussionsupporting
confidence: 93%
“…A few additional Israeli studies have reported on lack of disparities or even on pro-minority differences in care between Arabs and Jews. For example, a study of the unwarranted epidemic of benzodiazepine use in Israel, found that older Arab Israelis are much less likely to receive benzodiazepine or benzodiazepine-receptor agonists than older Jewish Israelis [ 18 ]. A national Israeli study on participation in health promotion workshops has found that although participation rates among Arabs were lower than among Jews, once enrolled in a workshop, Arabs tended to attend more meetings than Jews [ 19 ].…”
mentioning
confidence: 99%
“…Pain, agitation, worry and sadness were still found as reasons. In the other two studies, the first one shows that insomnia and anxiety were also the most frequent causes 25 and the second one reported that the diagnosis of depression was the most recurrent 26 .…”
Section: Discussionmentioning
confidence: 99%